Evaluasi Hasil Belajar Mahasiswa Melalui Pembelajaran Metode Studi Kasus Pada Mata Kuliah Perkembangan Peserta Didik di Program Studi Pendidikan IPA - Salma Samputri (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Evaluating learning outcomes across different class types remains a critical yet underexplored issue in Indonesian higher education, particularly in science teacher preparation programs where pedagogical equity is essential. This study evaluates student learning outcomes in the Child Development (PPD) course using the case study learning method at the Science Education Study Program, Universitas Negeri Makassar, during the Even Semester of Academic Year 2025–2026. A descriptive-quantitative approach with comparative case study design was employed. Research subjects consisted of 98 students across three classes: ICP Class (n=29), Regular Class A (n=36), and Regular Class B (n=33). Analysis encompassed descriptive statistics (mean, median, SD, skewness, kurtosis, 95% CI), Shapiro-Wilk normality test, Levene homogeneity test, One-Way ANOVA, Kruskal-Wallis as non-parametric alternative, and Mann-Whitney post-hoc tests with Bonferroni correction. Descriptive results showed mean scores of 87.79 (SD=6.59) for ICP, 87.17 (SD=4.87) for Regular A, and 88.09 (SD=3.47) for Regular B. Shapiro-Wilk test indicated non-normal distributions across all classes (p<.001), warranting Kruskal-Wallis as the primary test, which revealed no significant inter-class differences (H=1.039, p=.595). This was corroborated by One-Way ANOVA (F(2,95)=0.301, p=.741, η²=.006), indicating a trivial effect size. Mann-Whitney post-hoc comparisons with Bonferroni correction found no significant pairwise differences (all p>.017). These findings imply that case study method implementation in PPD produced equivalent and consistent learning outcomes across all three classes, with a classical completion rate of 98.0% (grade ≥B+).